2022
DOI: 10.1007/s11606-022-07480-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability on Shifting Ground: a Rapid Qualitative Assessment of Multi-institutional Inpatient Surge Planning and Workforce Deployment During the COVID-19 Pandemic

Abstract: Background During the initial wave of COVID-19 hospitalizations, care delivery and workforce adaptations were rapidly implemented. In response to subsequent surges of patients, institutions have deployed, modified, and/or discontinued their workforce plans. Objective Using rapid qualitative methods, we sought to explore hospitalists’ experiences with workforce deployment, types of clinicians deployed, and challenges encountered with subsequent iterations of surge planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Hiring additional staff as a measure to increase the supply of health workers supports the existing staff and prevent work overload. On the other hand, maximizing the utilization of the existing staff, through increasing the work shifts for example, can lead to staff burnout and to negative patient outcomes ( 12 , 23 , 24 ). In the United States of America (USA), a survey reported that the main reason for hiring temporary staff reported by more than 70% of health facilities during COVID-19 pandemic was to prevent the burnout of the existing staff ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hiring additional staff as a measure to increase the supply of health workers supports the existing staff and prevent work overload. On the other hand, maximizing the utilization of the existing staff, through increasing the work shifts for example, can lead to staff burnout and to negative patient outcomes ( 12 , 23 , 24 ). In the United States of America (USA), a survey reported that the main reason for hiring temporary staff reported by more than 70% of health facilities during COVID-19 pandemic was to prevent the burnout of the existing staff ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The focus groups were conducted in partnership with the Hospital Medicine Reengineering Network (HOMERuN) and included physicians, advanced practice providers, and hospital medicine researchers. The HOMERuN network is a collaborative of hospitals, hospitalists, and multidisciplinary care teams founded in 2011 that further supported joint efforts during the COVID‐19 pandemic 11–14 . The focus group session was facilitated by the workforce planning subgroup within the HOMERuN network.…”
Section: Methodsmentioning
confidence: 99%
“…The HOMERuN network is a collaborative of hospitals, hospitalists, and multidisciplinary care teams founded in 2011 that further supported joint efforts during the COVID-19 pandemic. [11][12][13][14] The focus group session was facilitated by the workforce planning subgroup within the HOMERuN network. To limit bias in participation, any employee (e.g., clinician, researcher, administrator, patient advocate) in a hospital medicine division who is interested in joining the network is able to participate.…”
Section: Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three focus groups were conducted concurrently as breakout rooms during the meeting as the main part of the agenda, as has been done previously. 27 Focus groups allowed participants to collaborate and build off each other's thoughts to generate ideas surrounding the topic, specifically environmental health. 28 The University of California San Francisco Institutional Review Board reviewed HOMERuN Collaborative Survey and Qualitative Research activities as "not human subjects research," study # 22-36424.…”
Section: Methodsmentioning
confidence: 99%